Correlation between Physical Fitness and Concentration of Gymnastics Athletes - Rion Hendrianto; Helmy Firmansyah (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
The purpose of the study was to examine the correlation between physical fitness and the concentration of West Java gymnastics athletes. The method used in this research was descriptive quantitative method with correlational design. The sampling technique used in this study was purposive sampling, involving seventeen young athletes (9 women and 8 men; age 19.71 ± 4.22 years, height 1.57 ± 0.07 m, body mass 52.4 ± 7 .58 kg) who were members of PPLP (Student Sport Education and Training Center) and Pelatda (Regional Training Center). The instruments used in this study were a physical condition test (sit and reach test, trunk lift test, standing stork test, whole body reaction, hurdle jump test, 12 core stability test, and beep test) for physical fitness and a concentration grid test for measuring concentration ability. The data processing and analysis results found a correlation of (r = 0.50 with a p-value of 0.0410.05) and a coefficient of determination of 25%. It concludes that there is a correlation between physical fitness and the concentration of West Java gymnastic athletes. Physical fitness is a crucial aspect for an athlete to meet the needs of movement and to perform optimal gymnastic movements without feeling excessive tired, so that they can maintain concentration when practicing or competing. Therefore, activities that can improve physical fitness are considered beneficial in increasing concentration abilities.